The effect of azolla on the yield of rice and fish grown in a rice-cum-fish culture system - Ferriol, Ophelia S. (College of Fisheries, University of the Philippines in the Visayas, 1985)
The effect of Azolla on the yield of rice and fish in a rice-cum-fish culture system was investigated at the Palawan National Agricultural College using Complete Randomized Design. Tilapia nilotica was used with IR-42 rice variety at the stocking density of 5000/ha and 1500/ha for the first and second trials, respectively. Two weeks after transplanting rice, fish were stocked and grown for 100 days. A treatment of Azolla with N, P and K had more tillers than other treatments. Percent and weight of filled grains should same trend as that of tiller count. Grain yield of rice was highest in Treatment I (N, P, K and azolla, rice with fish). This was followed by T3 (N, P, and K) rice with fish), T2 (P, K and azolla, rice with fish) and T4 (N, P, and K only, rice without fish). Also fish production was highest in Treatment I (153.52 kg/ha). This was followed by T2 (138.52 kg/ha) and T3 (126.11 kg/ha). Both trials showed the same trend. The final mean length and weight of fish registered similar trend as that of yield, i.e., highest in T1, followed by T2 and T3. Among treatments with fish the differences in fish production were not significant. Use of azolla both with and without N fertilizer showed increase income. When N was not applied but azolla added, the net income was higher by P115.56/ha. This is due to the higher cost of N fertilizer and lesser expense needed to produce azolla. Comparing T1 and T3 (which both had N, P, and K but azolla not added to T3), T1 had ahigher net return of P196.02 per ha. The results indicate that rice culture involved higher production cost than fish culture in rice paddies. The observations indicate that fish culture in rice paddies is profitable and can provide an additional net income of about P 846.20 /ha/crop. Despite of some area used for trenches, the results indicate that there was no decline in rice production per unit area. In fact, it seems that the benefit derived by putting fish in the trenches was high enough to offset the decrease in income even if the whole area was fully devoted to rice only.